Given g(x) is the integral from a to x of f(t) dt, we were able to derive that g'(x) = 1/h integral from x to x+h of f(t) dt. By the extreme value theorem there exists a min m and max M on [x,x+h] such that f(u) = m and f(v) = M and f(u)h<= integral x to x+h f(t) dt <= f(v)h (by properties of integrals). Dividing by h we get f(u)<= (g(x+h)- g(x)) / h <= f(v) by substitution. Here is where I'm confused, the text says if we let h--> 0 then u --> x and v--> x since u and v lie in [x,x+h]. I'm not understanding how u--> x and v--> x.
I'm self studying Stewart calculus and I'm working through the proof of FTC part 1. I'm stuck on a line in the proof that is preventing me from preceding.
Given g(x) is the integral from a to x of f(t) dt, we were able to derive that g'(x) = 1/h integral from x to x+h of f(t) dt.
By the extreme value theorem there exists a min m and max M on [x,x+h] such that f(u) = m and f(v) = M and f(u)h<= integral x to x+h f(t) dt <= f(v)h (by properties of integrals).
Dividing by h we get f(u)<= (g(x+h)- g(x)) / h <= f(v) by substitution.
Here is where I'm confused, the text says if we let h--> 0 then u --> x and v--> x since u and v lie in [x,x+h]. I'm not understanding how u--> x and v--> x. See 3rd image below, text is a red box.
![The Fundamental Theorem of Calculus, Part 1 If f is continuous on [a, b], then the
function g defined by
g(x) - S² (1) de a= x=b
is continuous on [a, b] and differentiable on (a, b), and g'(x)
Show Transcribed Text
2
that is,
g(x + h)
h
M.
Show Transcribed Text
3
g(x)
=
For now let's assume that h> 0. Since fis continuous on [x, x + h], the Extreme Value
Theorem says that there are numbers and in [x. x+h] such that f(u) m and
(v)M, where and M are the absolute minimum and maximum values of fon
[x, x + h]. (See Figure 6.)
By Property 8 of integrals, we have
Since h> 0, we can divide this inequality by h:
1 fath
mh=f(t) dt = Mh
S*** (1) dr
f(u) =
ATH
f(u)h = ™" f(t) dt = f(0)h
f(u) = = -1/2 √²+ h f(1) dt = f(v)
h
Now we use Equation 2 to replace the middle part of this inequality:
g(x + h) - g(x)
h
g
f(x).
= f(v)
Ĵ
Inequality 3 can be proved in a similar manner for the case where <0. (See Exercise 71.)
Now we let h→0. Then u→x and v→ x, since u and v lie between x and x + h.](/v2/_next/image?url=https%3A%2F%2Fcontent.bartleby.com%2Fqna-images%2Fquestion%2F819c1c1c-457a-4a93-a984-643be98554ff%2F1797e08f-1cf4-4b45-8005-2f9b393554fe%2F7765zl_processed.png&w=3840&q=75)
![](/static/compass_v2/shared-icons/check-mark.png)
Step by step
Solved in 2 steps
![Blurred answer](/static/compass_v2/solution-images/blurred-answer.jpg)
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
![Advanced Engineering Mathematics](https://www.bartleby.com/isbn_cover_images/9780470458365/9780470458365_smallCoverImage.gif)
![Numerical Methods for Engineers](https://www.bartleby.com/isbn_cover_images/9780073397924/9780073397924_smallCoverImage.gif)
![Introductory Mathematics for Engineering Applicat…](https://www.bartleby.com/isbn_cover_images/9781118141809/9781118141809_smallCoverImage.gif)
![Mathematics For Machine Technology](https://www.bartleby.com/isbn_cover_images/9781337798310/9781337798310_smallCoverImage.jpg)
![Basic Technical Mathematics](https://www.bartleby.com/isbn_cover_images/9780134437705/9780134437705_smallCoverImage.gif)
![Topology](https://www.bartleby.com/isbn_cover_images/9780134689517/9780134689517_smallCoverImage.gif)